Unlocking the motivational factors and psychographic profiles in umrah do it yourself (DIY) travel / Siti Atikah Rusli - Rusli, Siti Atikah (2024)
This present study examines the emergence of a new category religious travellers; namely Umrah Do-It-Yourself (DIY) travellers. Pilgrims, normally, hire specially licensed travel agents to make all the necessary arrangements for their Umrah, from booking the flights to arranging the trip's itinerary. However, a small segment of these pilgrims prefers to forgo hiring these agents and making their own travel arrangements. Furthermore, the Tourist e-Visa programme that the Saudi Arabian government launched in September 2019 has created a legal way of conducting a DIY Umrah. Extant studies on DIY travel have primarily examined backpackers, whose travel motivations are leisure or adventure, while those on religious tourism examined religious obligations. Furthermore, although there is increasing interest in Umrah DIY, the reasons for its increasing popularity among Umrah travellers remains elusive. Therefore, this present study aims to (i) explore the motivational factors that influence Umrah DIY travel satisfaction, (ii) examine the motivational factors that influence Umrah DIY travel satisfaction, (iii) identify the most dominant factors influencing the choice of Umrah DIY travel satisfaction, and (iv) define the psychographic profile of Umrah DIY based on the activities, interests, and opinions (AIO) approach. An exploratory sequential mixed method research (MMR) design and the theory of customer-dominant logic (CDL) was used as a guide to interview 20 respondents and purposively select 144 Umrah DIY travellers from a 10000 member Facebook forum to participate in questionnaire-based survey. Respondent participation was voluntary and each respondent was provided with a consent form and assured anonymity to ensure that the research was ethical. NVivo was used to analyse the interview data, IBM® SPSS® was used to conduct the preliminary and descriptive analyses of the survey data, and SmartPLS was used to develop a model. The interview findings indicate that Umrah travellers are most satisfied with the flexibility, budget travel, information sources, spirituality, familiarity, and companionship attributes of Umrah DIY travel. However, the survey findings do not indicate a significant correlation between Umrah DIY travel with budget travel, spirituality, and familiarity. Therefore, although the interviewees were satisfied by all of the aforementioned attributes, the survey findings indicate that Umrah DIY travellers are most satisfied by the budget travel, information sources, and, primarily, flexibility attributes of Umrah DIY travel. The quantitative survey data not only clarified the qualitative interview findings but highlighted that Umrah DIY travellers prefer Umrah DIY travel as it is flexible, which the respondents valued as it enabled them to construct their own itineraries according to their own individual preferences.